2019
DOI: 10.18632/oncotarget.27272
|View full text |Cite
|
Sign up to set email alerts
|

Sequential somatic mutations upon secondary anti-HER2 treatment resistance in metastatic ERBB2S310F mutated extramammary Paget’s disease

Abstract: Metastatic extramammary Paget’s disease is a rare adenocarcinoma with poor prognosis. Several reports of human epidermal growth factor receptor 2 alterations point to its pathogenic role in the disease. However, the occurrence of treatment resistance to anti-HER2 therapy demand the need for further knowledge. We report of a patient with metastatic penoscrotal extramammary Paget’s disease, with an ERBB2S310F mutation, in which near complete response was achieved upon treatment with trastuzumab and carboplatin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…In 2019, Nordmann TM reported a case with EMPD harboring HER2 S310F mutation, who achieved near-complete response after treatment with trastuzumab and carboplatin. 17 In the present study, we reported a novel HER2 gene alteration that these EMPD patients harbored triple uncommon HER2 mutations (R678Q/S310Y/S310F). Meanwhile, this patient showed a partial response to pyrotinib.…”
Section: Discussionmentioning
confidence: 52%
“…In 2019, Nordmann TM reported a case with EMPD harboring HER2 S310F mutation, who achieved near-complete response after treatment with trastuzumab and carboplatin. 17 In the present study, we reported a novel HER2 gene alteration that these EMPD patients harbored triple uncommon HER2 mutations (R678Q/S310Y/S310F). Meanwhile, this patient showed a partial response to pyrotinib.…”
Section: Discussionmentioning
confidence: 52%
“…8 This report describes three cases of metastatic and one case of recurrent HER2-positive vulvar Paget's disease effectively treated with weekly paclitaxel and trastuzumab. In addition to case reports of patients with HER2 positive, non-vulvar extramammary Paget's disease treated with anti-HER2 agents, [9][10][11][12][13][14] there are four separate case reports of women with metastatic HER2 positive vulvar Paget's disease treated similarly (online supplemental table). Our series, therefore, represents the largest number of reported cases of vulvar Paget's treated with these agents.…”
Section: Discussionmentioning
confidence: 99%
“…As described above, HER2 overexpression is frequently found in EMPD lesions, and HER2 may play crucial roles in the development and progression of EMPD in cases of HER2-positive tumors. Indeed, multiple cases of HER2-positive advanced EMPD have been reported that have shown the antitumor effects of anti-HER2 antibody, trastuzumab, monotherapy, or trastuzumab combined with other chemotherapies, such as paclitaxel or carboplatin [57,[143][144][145][146][147][148]. Most of these cases showed PFS of longer than 12 months, suggesting that anti-HER2 antibody is a promising therapy for advanced EMPD.…”
Section: Anti-her2 Antibody Therapymentioning
confidence: 99%